Dual stimuli-induced formation of a μ-hydroxido bridged [Zn9L5(μ-OH)6]12+ half-pipe. Issue 3 (30th November 2015) - Wood, Christopher S.; Ronson, Tanya K.; McConnell, Anna J.; Roberts, Derrick A.; Nitschke, Jonathan R.
Abstract : Low-symmetry metal–organic architectures that feature unusual binding motifs are useful for exploring new modes of guest recognition. Abstract : Low-symmetry metal–organic architectures that feature unusual binding motifs are useful for exploring new modes of guest recognition. Such structures remain difficult to create using current rational design principles. One approach to constructing such architectures is to employ ligands with coordination vectors oriented to preclude the formation of simple, low nuclearity molecular assemblies upon complexation to metal ions. Here we report two new supramolecular assemblies generated from such a ligand: a simple metastable [Zn3 L3 ] 6+ assembly, which was observed to convert to a more complex [Zn9 L5 (μ-OH)6 ] 12+ twisted half-pipe architecture. Two chemically distinct stimuli—an anionic template and a base—must be applied for the conversion to occur. Perchlorate, perrhenate, trifluoromethanesulfonate and 2-naphthalenesulfonate were found to act as competent templates for the [Zn9 L5 (μ-OH)6 ] 12+ structure.